Viability of the fungus Metarhizium anisopliae in mixture with agrochemicals - GONZÁLEZ-D., MARIA ELENA; VALBUENA-P., BLANCA FABIOLA; RIVERA-M., ARMANDO; BUSTILLO-P., ALEX ENRIQUE; CHAVES, BERNARDO (Revista Colombiana de Entomología, 1996)
In attempt to use the entomopathogenic fungus Metarhizium anisopliae as part of an integrated pest management program against the coffee berry borer, Hypothenemus hampei, the commercial (CD) and half commercial doses (1/2CD) of the following substances were tested to determine their effect on the fungus. Insecticides: endosulfan, clorpirifos, pirimifos methyl, fenitrothion, isazofos and neem; fungicides: benomyl, cyproconazol, hexaconazol, triadimefon and copper oxychloride; herbicides: oxyfluorfen, paraquat, glyfosate and glyfosate + terbutilazina; spray additives: Agral, Agrotin, Mezclafix and Mixel; foliar fertilizer: Tottal. The inhibition measured in percentage at 24 h after germination for the CD and 1/2CD was respectively, for the insecticides: pirimifos methyl (98.16 and 57.43%), clorpirifos (97.42 and 58.95%), fenitrothion (100 and 100%) and endosulfan (96.94 and 69.75%); for fungicides: cyproconazol (98.79 and 96.37%), hexaconazol (58.08 and 36.56%) and triamidefon (100 and 95.11%); for herbicides: oxyfluorfen (100 and 100%) and paraquat (99.06 and 98.80%); for spray additives: Mixel (43.06 y 28.93%). The other substances tested had less inhibitory effect (